Measurement of pO2 by luminescence lifetime spectroscopy: A comparative study of the phototoxicity and sensitivity of [Ru(Phen)3]2+ and PdTCPP in vivo. Issue 5 (2nd September 2016) - Huntosova, Veronika; Gerelli, Emmanuel; Horvath, Denis; Wagnieres, Georges
Abstract : Dysfunctions in tissue metabolism can be detected at early stages by oxygen partial pressure (pO2 ) measurement. The measurement of emission lifetimes offers very promising and non‐invasive approach to estimate pO2 in vivo . This study compares two extensively used oxygen sensors and assesses their in vivo oxygen sensitivity and phototoxic effect. Luminescence lifetime of Ru‐polypyridyl complex and of Pd‐porphyrin is measured in the Chick's Chorioallantoic Membrane (CAM) model with a dedicated optical fiber‐based, time‐resolved spectrometer. The Pd‐porphyrin luminescence lifetimes measured in the CAM model exposed to different pO2 levels are longer and have a broader dynamic range (10–100 μs) than those of Ru‐polypyridyl complex (0.6–1 μs). The combined statistical analysis based on an estimate of the kurtosis and skewness, bootstrapping method and routine normality tests is performed. The indicators of the averages and signal to noise ratio stability are also calculated. The combination of several data processing allows selection of the better sensor for a given application. In particular, it is found that the advantage of Ru‐polypyridyl complex over Pd‐porphyrin is two‐fold: i) Ru‐polypyridyl complex datasets have consistently better statistical characteristics, ii) Ru‐polypyridyl exhibits lower cytotoxicity. Abstract : In vivo and real‐time measurements of oxygen partial pressure are interesting for numerous applications, including cancer detection and treatment. This can be performed by time‐resolved luminescence spectroscopy of molecular probes. However, depending on the conditions, the oxygen sensitivity is poor and phototoxic effects are induced. In this paper we show that an advanced statistical analysis brings new insights for the selection of the optimal probe and measurement conditions.